ChemInform Abstract: Asymmetric Aza‐Michael Additions of 4‐Nitrophthalimide to Nitroalkenes and Preliminary Study of the Products for Herbicidal Activities. Issue 32 (18th July 2013) - Ma, Shijun; Wu, Lulu; Liu, Ming; Huang, Yaodong; Wang, Yongmei
Abstract For the first time the highly enantioselective title reaction using a readily available chiral catalyst is developed.